ЎЗБЕК ДЕТЕКТИВ НАСРИДА ЖИНОЯТ ВА ЖАЗО МУАММОСИ ҲАМДА СЮЖЕТ СХЕМАСИ - Халилова, Д.Ж. (SCIENCE and SOCIETY, 2023)
This article are interpreted the features of detectiveism and criminalism used in psychological, social, philosophical, domestic works in Uzbek literature.
Keywords: detectiveism; criminology; "microcriminal plot"; "microdetective reality"; psychological effect; psychological imagination